1995
DOI: 10.1182/blood.v86.3.1035.1035
|View full text |Cite
|
Sign up to set email alerts
|

Role of the glycoprotein Ib-binding A1 repeat and the RGD sequence in platelet adhesion to human recombinant von Willebrand factor

Abstract: To assess the relative importance of the glycoprotein (GP) Ib binding domain and the RGDS binding site in platelet adhesion to isolated von Willebrand factor (vWF) and to collagen preincubated with vWF, we deleted the A1 domain yielding delta A1-vWF and introduced an aspartate- to-glycine substitution in the RGDS sequence by site-directed mutagenesis (RGGS-vWF). Recombinant delta A1-vWF and RGGS-vWF, purified from transfected baby hamster kidney cells, were compared with recombinant wild-type vWF (WT-vWF) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 36 publications
7
34
1
Order By: Relevance
“…The results showed vWF undergoes a globular to extended chain conformational transition on a hydrophobic surface in the shear stress regime of 35 + 3.5 dyn/cm 2 . This corresponds to a wall shear rate in blood of ~1,000 s -1 , similar to the range of shear that vWF predominates over fibrinogen as the principal mediator of platelet adhesion [90]. These data are presented in (Fig.…”
Section: Von Willebrand Factor (Vwf)mentioning
confidence: 57%
“…The results showed vWF undergoes a globular to extended chain conformational transition on a hydrophobic surface in the shear stress regime of 35 + 3.5 dyn/cm 2 . This corresponds to a wall shear rate in blood of ~1,000 s -1 , similar to the range of shear that vWF predominates over fibrinogen as the principal mediator of platelet adhesion [90]. These data are presented in (Fig.…”
Section: Von Willebrand Factor (Vwf)mentioning
confidence: 57%
“…Results showed that this mAb was able to completely block CHO‐αIIbβ3 cell adhesion and spreading on VWF (Fig 2). This was confirmed by showing that DTT‐treated CHO‐αIIbβ3 cells were unable to adhere and spread on rVWF‐RGGS (data not shown), reported as unable to bind to thrombin‐stimulated platelets (Lankhof et al , 1995).…”
Section: Inhibition Of Dtt‐stimulated Cho‐αiibβ3 Cell Adhesion and Spmentioning
confidence: 68%
“…These recombinant variants were used to analyze ADAMTS‐13‐mediated proteolysis. Plasmids pNUT‐VWF encoding wt‐VWF, rVWF/C1130F, rVWF/C1149R and rVWF/C2671Y were stably expressed in baby hamster kidney‐cells overexpressing furin for proper removal of the propeptide [7,18,19]. cDNA encoding wt‐VWF was subcloned into pcDNA6 for co‐transfection to rVWF/C1149R‐expression cells, allowing selection using blasticidin to establish stable cell‐lines expressing heterozygous wt‐VWF‐rVWF/C1149R.…”
Section: Methodsmentioning
confidence: 99%